Analisis Keputusan Perusahaan Manufaktur Dalam Melakukan Pergantian Kantor Akuntan Publik (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014) - Anisa, Norma (2016)
Independence of the public accounting firm will fade when the suspect had long-standing relationships with its clients. One way to keep independence auditor is to make turn public accounting firm. Several previous studies showed the results of different studies. This study aims to examine the factors that influence the turn of public accounting firms in manufacturing companies with a view of the client side The population used in this research is manufacturing companies listed on BEI in the year 2012-2014.The data used in this research is secondary data and data collection is done using purposive sampling method.The number of samples collected as many as 63 companies.Data analysis technique used is logistic regression. The results of the analysis of this model shows that a change of management, financial distress and affect the management share ownership change of public accounting firms.By contrast, the growth rate of the company, the dividend policy and the number of commissioners did not affect the change of public accounting firms.This means that a change of public accounting firms affected by the change of management, financial distress and stock ownership management. Keywords:substitution kap, management turnover, financial distress, the growth of the company, management share ownership, dividend policy and the number of commissioners.